Efektivitas Kurikulum Pendidikan Islam dalam Membentuk Karakter Siswa di Sekolah Islam Terpadu - Ghina Fadlilah Sukmara; Opik Taupik Kurahman; Dadan Rusmana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the effectiveness of the Islamic Education curriculum in shaping students' characters at Integrated Islamic Schools (SIT). The main focus of this study is on a holistic approach involving academic, extracurricular, and school environment aspects. This study uses a qualitative approach with a case study method, and data were collected through in-depth interviews and participatory observations. The results of the study indicate that the integration of Islamic values ​​in the curriculum, such as honesty, responsibility, and caring, has succeeded in shaping students' characters. Excellent programs such as recitation & tahfizh of the Qur'an and Islamic character development play an important role in shaping students' attitudes and behaviors. The role of teachers as role models and family support also greatly influence the success of character education. Continuous evaluation provides insight into the strengths and weaknesses of the curriculum, as well as improvements that need to be made. This study confirms that the Islamic Education curriculum at SIT is effective in shaping students' characters, which has a positive impact on their social behavior and academic achievement. These findings provide recommendations for the development of a more effective curriculum in facing the challenges of the times.